A comprehensive review of smart campus frameworks, technological innovations, and user-centric challenges: Toward sustainable and inclusive implementation - Ismail @ Che Wan Mahmud, Ronizam; Ishak, Nadiah; Zainol, Norzaimah; Ab Rahman, Suzana; Abd Rahman, Nurul Afiqah; Mohd Aboobaider, Burhanuddin (Human Resource Management Academic Research Society, 2025)
The smart campus paradigm represents a transformative approach in higher education, wherein advanced technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), blockchain, edge computing, and Industry 4.0 innovations are integrated into institutional infrastructures to develop intelligent, sustainable, and user-oriented environments that optimize operational efficiency, resource management, and pedagogical practices. This literature review critically analyses the evolution of smart campus frameworks, emphasizing models such as Polin’s Smart Campus Assessment Framework and Min-Allah’s generic model, which, despite offering valuable theoretical contributions, remain constrained by limited empirical validation and insufficient testing across varied institutional and cultural contexts. Technological progress has facilitated notable improvements in domains such as energy efficiency, campus security, personalized learning, and data-driven governance; however, extant research predominantly prioritizes technological dimensions while underrepresenting the social, cultural, and behavioural aspects of user engagement, particularly with respect to the experiences and perceptions of students, faculty, and administrative personnel. Evidence from user satisfaction studies underscores the necessity of a comprehensive, multistakeholder perspective that aligns technological innovation with human needs, while regional case studies further highlight the influence of socio-economic and cultural variables on the adoption and success of smart campus initiatives. Despite substantial scholarly attention, critical research gaps persist, notably the empirical validation of proposed frameworks, the systematic integration of user-cantered design principles, and the reconciliation of technological advancement with inclusivity, accessibility, and sustainability imperatives. Accordingly, future research should prioritize the intersection of technological innovation and human-centred application to advance smart campuses that are not only technologically sophisticated but also socially responsive, culturally adaptive, and sustainable within the global higher education landscape.